2007
DOI: 10.1161/circulationaha.106.666008
|View full text |Cite
|
Sign up to set email alerts
|

Negative Inotropy of the Gastric Proton Pump Inhibitor Pantoprazole in Myocardium From Humans and Rabbits

Abstract: Background-Proton pump inhibitors are used extensively for acid-related gastrointestinal diseases. Their effect on cardiac contractility has not been assessed directly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
52
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(54 citation statements)
references
References 30 publications
1
52
1
Order By: Relevance
“…Contrary to a majority of reports [21][22][23][24], our study demonstrated that PPZ inhibited protein expression of HIF-1α in an optimal dosage manner, or else a dramatic wording of "break point", instead of dose-dependent mode. This may be because the effects of PPZ on tumor cells are not only through the changing levels of HIF-1α; as a matter of fact, the concrete mechanism is not yet clarified.…”
Section: Discussioncontrasting
confidence: 99%
“…Contrary to a majority of reports [21][22][23][24], our study demonstrated that PPZ inhibited protein expression of HIF-1α in an optimal dosage manner, or else a dramatic wording of "break point", instead of dose-dependent mode. This may be because the effects of PPZ on tumor cells are not only through the changing levels of HIF-1α; as a matter of fact, the concrete mechanism is not yet clarified.…”
Section: Discussioncontrasting
confidence: 99%
“…5 Schillinger et alhave evaluated the effects of PPIs (specifically pantoprazole) on myocardial tissue specimens from humans and rabbits. 1 Human tissue was derived from 8 patients undergoing heart transplantation (failing ventricular tissue) and 16 patients undergoing cardiac surgery (nonfailing atrial tissue). In both specimen types, there was a dose-dependent effect of decreased isometric twitch force with pantoprazole exposure and partial reversibility after drug washout.…”
Section: Discussionmentioning
confidence: 99%
“…Ex vivo data suggest that in myocardial tissue, this enzyme may regulate homeostasis of H+ and K+, and its suppression could cause cellular acidosis, interfere with Ca+ responsiveness in the muscle cells, and thereby depress myocardial contractility. 1 It is not clear if the negative inotropic effect observed in these in vitro studies translates into clinically relevant consequences in acutely ill patients. We accordingly sought to evaluate the acute hemodynamic impact of PPI administration in these patients.…”
Section: Introductionmentioning
confidence: 99%
“…Both animal and human tissue studies have shown that PPIs have electrophysiological effects, [23] potentially by increasing intracellular calcium concentrations [4]. Calcium concentration is an important factor in myocytes automaticity and focal arrhythmias are usually secondary to increased automaticity.…”
Section: Serum Potassium (Meq/l) (C)mentioning
confidence: 99%
“…The H+/K+ ATPase has also been isolated in myocardial and vascular smooth muscle cells. Ex vivo data suggest that in myocardial tissue, this enzyme may regulate homeostasis of H+ and K+, and its suppression could cause cellular acidosis, interfere with Ca+ responsiveness in the muscle cells, and thereby depress myocardial contractility [4]. On the other hand, Gomes et al [5] found that the administration of pantoprazole before induction of ischemia significantly protected the myocardial functional recovery in isolated rat heart.…”
Section: Introductionmentioning
confidence: 99%